Problematyka tożsamości narodowej Kosowskich Albańczyków w świetle pilotażowych (wstępnych) badań terenowych – wprowadzenie do dalszych analiz (Politeja, 2022)
THE ISSUE OF NATIONAL IDENTITY OF KOSOVAR ALBANIANS IN THE LIGHT OF PILOT (PRELIMINARY) FIELD STUDIES – AN INTRODUCTION TO FURTHER ANALYSESThe article deals with the dilemmas of the national identity of Kosovar Albanians. The author presents this problem from the perspective of selected scientific theories and presents the results of empirical research. The text consists of two main parts (theoretical and practical). The theoretical part was divided into two parts. The first includes considerations on the concept of identity in social sciences, and the second foucuses on the analysis of the concept of national identity (selected concepts). The research part presents the results of empirical research related to the level of self-identification in terms of national identity of Kosovar Albanians. The text opens with an introduction and instead of the ending, the author includes a symbolic quote.